YELLOW : Tentoonstelling over actuele kunst en psychiatrie. - Cuypers, Kris; De Vlieghere, Dieter; Hoet, Jan; Stouthuysen, Robert (Geel Gent : Janssen Pharmaceutica Beerse Openbaar Psychiatrisch Ziekenhuis Geel SMAK (Stedelijk Museum voor Actuele Kunst) Gent, 2001)
Barry, Orla ; De Bruyckere, Berlinde ; de Cordier, Thierry ; DC, Franky ; Delrue, Ronny ; Derive, Herman ; Devriendt, Robert ; Dietvorst, Els ; Fink, Christoph ; Hollander, Jeroen ; Van Imschoot, Jan ; Janke, Karl Hans ; Krüsi, Hans ; Nauman, Bruce ; Panamarenko ; Rhoades, Jason ; Rombouts, Guy ; Schmidt, Marianna ; De Schrijver, Freddy ; Theys, Koen ; Tonnard, Philippe
Engels
Nederlands
Exhibition. YELLOW. Pas 204 Geel. Openbaar Psychiatrisch Ziekenhuis Geel. 2001-05-20. 2001-07-15
boek